The Effect of Packaging Design and Instagram Promotional Visuals on the Purchase Intention of Baytat Cinda Cakes in Manna - Secilia Racmi; Nia Indriasari; Yun Fitriano (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of packaging design and Instagram promotional visuals on consumer purchase intention for Baytat Cinda cakes in Manna, South Bengkulu. Data analysis in this study was conducted quantitatively using multiple linear regression analysis. This method was chosen based on the research objective, which was to explain the causal relationship between the independent variables, namely packaging design (X1) and promotional visuals (X2), and the dependent variable, namely purchase intention (Y), of Baytat Cinda consumers in Manna, South Bengkulu. The results showed that all questionnaire items were valid and reliable. The regression equation obtained was Y = 1.476 + 0.316X₁ + 0.608X₂, indicating that packaging design and Instagram promotional visuals had a positive effect on purchase intention. The R² value of 0.692 indicates that these two variables explain 69.2% of the variation in purchase intention, while 30.8% is influenced by other factors outside the study. Partial tests showed that packaging design (t = 2.704; sig. = 0.009) and Instagram promotional visuals (t = 5.523; sig. = 0.000) had a positive and significant effect on purchase intention. Simultaneous tests (F count = 80.981 > 3.12; sig. = 0.000) proved that both variables together significantly influenced purchase intention.